2019
DOI: 10.1128/mbio.02678-19
|View full text |Cite
|
Sign up to set email alerts
|

Reassessing the Role of the Type II MqsRA Toxin-Antitoxin System in Stress Response and Biofilm Formation: mqsA Is Transcriptionally Uncoupled from mqsR

Abstract: There is growing controversy regarding the role of chromosomal toxin-antitoxin systems in bacterial physiology. mqsRA is a peculiar toxin-antitoxin system, as the gene encoding the toxin precedes that of the antitoxin. This system was previously shown to play a role in stress response and biofilm formation. In this work, we identified two promoters specifically driving the constitutive expression of the antitoxin, thereby decoupling the expression of antitoxin from the toxin. We also showed that mqsRA contribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
57
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(61 citation statements)
references
References 75 publications
4
57
0
Order By: Relevance
“…However, the authors found that yefM-yoeB-induced cleavage at 42°C was not correlated with growth inhibition and that yefM-yoeB did not give any fitness advantage or disadvantage when cells were grown at this temperature (114). Finally, another study showed that the MqsA antitoxin is rapidly degraded by Lon under oxidative stress (115), which was not reproduced by a subsequent study (53). To conclude, antitoxin proteolysis under stress conditions, leading to TA system activation, is far from being a general rule, and further research is needed to better understand the conditions leading to TA systems induction and phenotypes, probably on a case-by-case basis.…”
Section: Activation Of Ta Systems: From Regulation To Phenotypesmentioning
confidence: 90%
See 3 more Smart Citations
“…However, the authors found that yefM-yoeB-induced cleavage at 42°C was not correlated with growth inhibition and that yefM-yoeB did not give any fitness advantage or disadvantage when cells were grown at this temperature (114). Finally, another study showed that the MqsA antitoxin is rapidly degraded by Lon under oxidative stress (115), which was not reproduced by a subsequent study (53). To conclude, antitoxin proteolysis under stress conditions, leading to TA system activation, is far from being a general rule, and further research is needed to better understand the conditions leading to TA systems induction and phenotypes, probably on a case-by-case basis.…”
Section: Activation Of Ta Systems: From Regulation To Phenotypesmentioning
confidence: 90%
“…Later on, the mqsRA system in E. coli was found to regulate a variety of biological processes such as biofilm formation and response to oxidative stress, notably by the capacity of the antitoxin MqsA to regulate expression of master regulators such as csgD or rpoS (51,52). However, none of these phenotypes or regulations could be reproduced in an independent study (53). All of these observations call into question the implication of TA modules in various stress responses, whether through PCD, translation inhibition, or pleiotropic regulation.…”
Section: Proposed Functions: the Many Faces Of Ta Systemsmentioning
confidence: 99%
See 2 more Smart Citations
“…Non-growing bacteria are known to be protected from environmental insults 51-53 even if they do not actively combat with stress, as appears to be the case, for example, with most antibiotic-tolerant persister cells 54 . However, despite the potential of TA-encoded toxins to protect bacteria, the deletion of whole TA loci does not usually affect the bacterial fitness 20,27-30,55 , leaving the question of TA systems’ importance in stress tolerance still open.…”
Section: Discussionmentioning
confidence: 99%